Editorial (Transactions of the Association of European Schools of Planning, 2020)
This issue of Transactions of AESOP brings together a series of papers which reflect on the European Spatial Development Perspective (ESDP) document which was adopted by the then member states of the European Union (EU) in Potsdam, Germany in 1999, and is published shortly after the adoption in December 2020 of a new EU Territorial Agenda 2030 document under the recent German EU Presidency. It features an introduction and five original papers which explore the legacies of the ESDP and the present and future prospects for European territorial development and urban policy.